Posted by **Satrianna** on Saturday, January 19, 2013 at 4:45pm.

3x^2+6x/2x^2-11x+12 - 2x^2-5x+3/x^2+x-2 ÷ 4x^2-12x+9/x^2-4

I got

3x^3+2x^2-12x+8 / (x-1)(2x-3) (x-4)

Is this right please show your steps so I can understand!

Thanks I greatly appreciate your help!

Iwas just wondering wen my question be answered...thanks

## Answer this Question

## Related Questions

- Hard algebra qestion - 3x^2+6x/2x^2-11x+12 - 2x^2-5x+3/x^2+x-2 ÷ 4x^2-12x+9/x^2-...
- math - I solved this problem 12x-6=11x -6+6=0 11x+6 12x=11x+6 12x-11x=x 11x-11x=...
- algebra - Can anyone tell me if I got this problem right 12x-6=11x 12x-6+6=11x+6...
- Urgent Math please check - Very Important I can get someone to check these for ...
- Algebra - What is the side length of a square with an area of 144x²? A.12 B.12x ...
- Polynomial- Doublecheck2 - I asked this earlier, but I didn't get an answer. I'm...
- math - simplify and state any restrictions: 1. x+3/x^2+11x+24 - 2x+10/x^2+11x+30...
- algebra1 - could you walk-through the steps to solving this problem because I am...
- algebra - find a third degree polynomial equation with coefficients that has ...
- Math - you know that 8x = 5y you know that 3y=14z since 5 = (5/3)*3, 5y = (5/3...